Study of Cardiac Troponin I level in Acute Coronary Syndrome and its correlation with Left Ventricular Systolic Function (Cardiovascular Journal, 2019)
Background: In the diagnosis of acute coronary syndrome, cardiac troponin I is highly reliable and widely available biomarker. Serum level of cardiac troponin I is related to amount of myocardial damage and also closely relates to infarct size. Our aim of the study is to find out the relationship between cardiac troponin I and left ventricular systolic function after acute coronary syndrome.Methods: Total of 132 acute coronary syndrome patients were included in this study after admission in coronary care unit of Sir Salimullah Medical College, Mitford Hospital. Troponin I level was measured at admission and left ventricular ejection fraction (LVEF) was measured by echocardiography between 12-48 hours of onset of chest pain.Results: There was negative correlation between Troponin I at 12 to 48 hours of chest pain with LVEF in these study patients. With a cutoff value of troponin I e”6.8 ng/ml in STEMI patients there is a significant negative relation between 12 to 48 hrs troponin I and LVEF (p